2009
DOI: 10.17221/1725-cjas
|View full text |Cite
|
Sign up to set email alerts
|

Effects of grass species on ruminal degradability of silages and prediction of dry matter effective degradability

Abstract: Forty samples of grass silages, made from the five most widely used grass species in ruminant nutrition (Dactylis glomerata L., Phleum pratense L., Lolium perenne L., Festuca arundinacea L. and hybrid Felina) were tested in the present study. These grass species conserved by an ensiling process were compared among each other according to dry matter (DM) rumen degradability parameters (a = portion of DM solubilized at initiation of incubation, b = fraction of DM potentially degradable in the rumen, c = rate con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
12
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 34 publications
2
12
1
Order By: Relevance
“…Degradability of organic matter in other disciplines is investigated particularly from the aspect of resistance in acid hydrolysis (Rovira and Vallejo, 2002;Shirato and Yokozava, 2006) or in oxidation (Blair et al, 1995;Chan et al, 2001). Because it determines the reaction time of organic matter transformations, it plays an important role in many practical applications (Frelich et al, 2009;Jančík et al, 2009;Hanuš et al, 2010;Jurajda et al, 2010;Váradyová et al, 2010).…”
mentioning
confidence: 99%
“…Degradability of organic matter in other disciplines is investigated particularly from the aspect of resistance in acid hydrolysis (Rovira and Vallejo, 2002;Shirato and Yokozava, 2006) or in oxidation (Blair et al, 1995;Chan et al, 2001). Because it determines the reaction time of organic matter transformations, it plays an important role in many practical applications (Frelich et al, 2009;Jančík et al, 2009;Hanuš et al, 2010;Jurajda et al, 2010;Váradyová et al, 2010).…”
mentioning
confidence: 99%
“…ED DM was best predicted by NDF (R 2 = 0.878), although all presented equations gave satisfactory predictions. NDF was also detected as the best ED DM predictor for grass silages by Jančík et al (2009). Nousiainen et al (2003a) found ADF as the best single predictor of organic matter digestibility of grass silages.…”
Section: Resultsmentioning
confidence: 94%
“…Prediction equations based on chemical composition have been successfully applied for different feeds and nutrients (Nousiainen et al, 2003a;Yan and Agnew, 2004;Andrés et al, 2005;Jančík et al, 2009;Villamide et al, 2009). However, adequate equations to predict DM and NDF rumen degradation parameters of grasses from chemical composition are lacking.…”
Section: Ruminal Degradability Of Dry Matter and Neutral Detergent Fimentioning
confidence: 99%
“…The in sacco analysis, which has been applied in the present study, is the most frequently used method for determination of degradability of DM, organic matter (OM), protein, fibre, minerals and other nutrients of feeds (Jančík et al, 2009).…”
mentioning
confidence: 99%